Socio-Clinical Profile Of HIV Patients Visiting To An Art Centre - Singh, Ajaypal; Singh, S; Alawa, HL (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2014)
Introduction: Scenario of the AIDS epidemic, clinical course and pattern of opportunistic infections in HIV patients is changing world-wide. The study aims to fulfill the paucity of socio-clinical profi le among the patient of HIV with geographical population of this region. Methodology: This is a hospital based cross sectional clinical study with a sample size of 110 respondents presenting to ART center at Jayarogya Hospital (JAH) Gwalior from May 2010 to Oct 2011. Results: Mean age of study population was 35.44±9. High Frequency of weight loss > 10% (P<0.001), fever (P=0.0027), breathlessness (P=0.03), itching (P<0.001), lymphadenopathy (P<0.001), oral thrush (P=0.006), extra pulmonary tuberculosis (P=0.04), candidiasis (P=0.006) at low CD4 count (<200) and difference in mean CD4 count (P=0.0039) among male (202.21) and female (291.41) was found to be statistically signifi cant. CD4 counts of the patients were signifi cantly inversely correlated with the number of opportunistic infections and the number of symptoms (R=-0.369; P<0.001, R=-0.223; P=0.019 respectively). Conclusion: The study depicts male predominance, young sexually active group vulnerability, with a quite difference in clinical presentation and occurrence of opportunistic infections from other part of the world necessitating formulation of different set of guidelines for subjects of Indian subcontinent to improve life-span of such patients. SAARC Journal of Tuberculosis, Lung Diseases & HIV/AIDS; 2013; X(2); 7-14 DOI: http://dx.doi.org/10.3126/saarctb.v10i2.9707